2017
DOI: 10.1051/0004-6361/201629125
|View full text |Cite
|
Sign up to set email alerts
|

Establishing binarity amongst Galactic RV Tauri stars with a disc

Abstract: Context. During the last few decades, it became more evident that binarity is a prevalent phenomenon amongst RV Tauri stars with a disc. This study is a contribution in comprehending the role of binarity upon late stages of stellar evolution. Aims. In this paper we determine the binary status of six Galactic RV Tauri stars, namely DY Ori, EP Lyr, HP Lyr, IRAS 17038−4815, IRAS 09144−4933 and TW Cam, which are surrounded by a dusty disc. The radial velocities are contaminated by high amplitude pulsations. We dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 69 publications
4
91
0
Order By: Relevance
“…The RVT stars that show IR excess are brighter in W than those without (also remarked by Manick et al (2017)), but excluding those there is well defined W(VI) relation for BLH, WVIR and non-dusty RVT, as illustrated in Figure 1.…”
Section: Period -Luminosity Relationmentioning
confidence: 87%
“…The RVT stars that show IR excess are brighter in W than those without (also remarked by Manick et al (2017)), but excluding those there is well defined W(VI) relation for BLH, WVIR and non-dusty RVT, as illustrated in Figure 1.…”
Section: Period -Luminosity Relationmentioning
confidence: 87%
“…9 the period-eccentricity distribution of post-AGB (pAGB) binaries are plotted. This sample contains dusty pAGB binaries with known orbital parameters from Waters et al (1993); Van Winckel et al (1995); Pollard et al (1996); Gonzalez & Wallerstein (1996); Van Winckel et al (1998, 1999; Maas et al (2002Maas et al ( , 2005 Manick et al (2017), and barium (Ba) and Tcpoor S stars for which orbital parameters were derived by Van der Swaelmen et al (2017). The Ba stars are giant stars in binary systems with a WD companion where the giant has an overabundance in s-process elements caused by mass transfer from WD progenitor during its AGB phase (Bidelman & Keenan 1951;Jorissen et al 1998).…”
Section: Period-eccentricity Of Post-agb Systemsmentioning
confidence: 99%
“…9. The period-eccentricity distribution of different types of post-AGB binaries that have undergone a mass-loss phase in their past: dusty pAGB binaries (green squares, Waters et al 1993;Van Winckel et al 1995;Pollard et al 1996;Gonzalez & Wallerstein 1996;Van Winckel et al 1998, 1999Maas et al 2002Maas et al , 2005Van Winckel 2007;van Winckel et al 2009;Gorlova et al 2014;Gezer et al 2015;De Smedt et al 2016;Manick et al 2017), Ba stars (blue circles, Van der Swaelmen et al 2017), Tc-poor S stars (black x's, Van der Swaelmen et al 2017) and the wide sdB binaries (red crosses, this article). See section 6.2.…”
Section: Period-eccentricity Of Post-agb Systemsmentioning
confidence: 99%
“…The classical picture of the theory of stellar evolution suggests that the progenitors of T2Cs evolve redward from the blue edge of the HB and may move up the Asymptotic Giant Branch (AGB) going through the BL Her-type and W Vir-type pulsation stages (Gingold 1985;Wallerstein 2002). However, recent work by Gezer et al (2015); Groenewegen & Jurkovic (2017a,b); Manick et al (2017) among others questions this classical picture and the origin and evolution of T2Cs is not as well-understood as was once thought to be. Iwanek et al (2018) confirmed BL Her stars to be as old as RR Lyraes while W Vir stars could be a mixture of old and intermediate-age stars.…”
mentioning
confidence: 99%